2021
DOI: 10.1017/s0033291721003810
|View full text |Cite
|
Sign up to set email alerts
|

The priming effect of repetitive transcranial magnetic stimulation on clinical response to electroconvulsive therapy in treatment-resistant depression: a randomized, double-blind, sham-controlled study

Abstract: Background Electroconvulsive therapy (ECT) is one of the most effective treatments for treatment-resistant depression (TRD). However, due to response delay and cognitive impairment, ECT remains an imperfect treatment. Compared to ECT, repetitive transcranial magnetic stimulation (rTMS) is less effective at treating severe depression, but has the advantage of being quick, easy to use, and producing almost no side effects. In this study, our objective was to assess the priming effect of rTMS sessions before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Buday et al found that this strategy resulted in a significantly lower seizure threshold after administering TMS over the dorsolateral prefrontal cortex (DLPFC) 30–80 minutes prior to ECT treatment 48 . Similarly, Rothermel et al found a significantly greater percentage improvement on the HDRS and that a lower electrical charge was needed for stimulation using this method compared to standard ECT 49 . There was no significant difference in cognitive SEs between treatment groups.…”
Section: Ect Augmentationmentioning
confidence: 84%
“…Buday et al found that this strategy resulted in a significantly lower seizure threshold after administering TMS over the dorsolateral prefrontal cortex (DLPFC) 30–80 minutes prior to ECT treatment 48 . Similarly, Rothermel et al found a significantly greater percentage improvement on the HDRS and that a lower electrical charge was needed for stimulation using this method compared to standard ECT 49 . There was no significant difference in cognitive SEs between treatment groups.…”
Section: Ect Augmentationmentioning
confidence: 84%
“…[ 10 ] On the other side, in terms of physical neuromodulation, it could be a promising substitute or supplement for drug therapy based on the irritability of neurons and plasticity of synapses, [ 11 ] and currently, transcranial magnetic stimulation (TMS) has been relatively widely accepted in clinic for the treatments of insomnia, depressive disorder, and so on, with its merits of noninvasiveness and painlessness. [ 12 ] Unfortunately, the uneven skull attenuation, the mismatch between bulky machines and blurred scalp markers, as well as the traditional reliance on manual coil movement and parameter adaption, unsurprisingly impose restrictions on the accuracy of stimulation, making the exact therapeutic effects far from satisfaction. [ 13 ] All these challenges prompt scientists to exploit innovative technologies with improved temporal‐spatial precision for NDs, to improve curative efficacy, reduce dosage and off‐target side effects, ensure security and convenience, and alleviate the burden of medical workers.…”
Section: Introductionmentioning
confidence: 99%
“…Priming is one such technique, where high-frequency (usually 6 Hz) rTMS is being administered immediately before administering low-frequency rTMS, to enhance the neural response to low-frequency rTMS. [14][15][16] Till-date, there has been no guideline, recommendation, or consensus with regards to the rTMS protocol to be used in LLD. High-frequency rTMS over left DLPFC is the US FDA (United States, Food and Drug Administration) approved protocol for major depression in adults 17 and also it is the most studied protocol in LLD, but has yielded mixed results.…”
Section: Introductionmentioning
confidence: 99%